Young Peasant Having Her Coffee from Pissarro Paintings and Works on Paper from the Art Institute of Chicago - Groom, Gloria (Art Institute of Chicago, 2015)
This entry features in-depth research on Pissarro's Young Peasant Having Her Coffee, drawing fascinating connections between Pissarro's life and work, and offering novel insights into his technique, showing how he consistently pushed Impressionist approaches in new directions. For more in-depth conservation research and interactive images, see the full catalogue at www.artic.edu/digitalpissarro.